Transformasi Norma Nusyuz menurut Kitab Fikih dalam Kompilasi Hukum Islam di Indonesia - Rizal Maulana Rahman (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Nusyuz according to the Qur'an, hadith and opinions of fiqh experts in their books, compilations of Islamic law that serve as guidelines in religious courts and as references are fiqh books, the concept of nusyuz according to the Compilation of Islamic Law is mentioned with the obligations of a wife who must obey or obedient to her husband and if the wife leaves her obedience or disobeys her husband, the husband's obligations such as providing for his wife fall except for the interests of his child, but the husband's obligation can return if the wife has not done nusyuz. The transformation from the book of fiqh into the Compilation of Islamic Law begins with the wife's nusyuz contained in the books of Fathul Mu'in and Bidayatul Mujtahid about providing a living from a husband to a wife who is nusyuz contained in article 80 paragraph 7, and the husband's obligation to fall to a wife who is nusyuz in article 84 paragraph 2 Meanwhile, from the husband if he does nusyuz it is not listed in the Compilation of Islamic Law, but in the book of fathul mu'in the obligation that the husband cannot afford to give to his wife in providing clothing, food, feed, apart from that in the book of Al-Wajiz it is stated that the husband's nusyuz by treating and molested his wife. Abstrak. Nusyuz menurut Al Qur’an, hadist dan pendapat ahli fikih dalam kitab-kitabnya, kompilasi hukum islam yang menjadi pedoman di pengadilan agama dan sebagai rujukannya adalah kitab-kitab fikih, Konsep nusyuz menurut Kompilasi Hukum Islam disebutkan dengan kewajiban seorang istri yang harus mentaati atau patuh terhadap suaminya dan jika istri keluar dari ketaatannya atau membangkang kepada suaminya maka kewajiban suami seperti menafkahi istrinya gugur kecuali kepada kepentingan anaknya, tetapi kewajiban suami dapat kembali apabila istri sudah tidak melakukan nusyuz. Transformasi dari kitab fikih kedalam Kompilasi Hukum Islam diawali nusyuz istri terdapat dalam kitab Fathul Mu’in dan Bidayatul Mujtahid tentang memberikan nafkah dari suami kepada istri yang nusyuz terdapat pada pasal 80 ayat 7, dan kewajiban suami gugur terhadap istri yang nusyuz pada pasal 84 ayat 2. Sedangkan dari suami jika berbuat nusyuz tidak dicantumkan dalam Kompilasi Hukum Islam akan tetapi dalam kitab fathul mu’in kewajiban yang tidak mampu diberikan suami kepada istri dalam memberikan sandang, pangan, pakan, selain dari itu dalam kitab Al-Wajiz disebutkan nusyuz suami dengan memperlakukan dan menganiaya istri.